Effect of long-term application of NP chemical fertilizer on soil exchangeable Mg distribution and accumulation under different cropping systems - WEI Feng; HAO Ming-de (浙江大学学报. 农业与生命科学版, 2012)
To understand the effects of different cropping systems on soil exchangeable Mg, samples of soil profiles under six types of different cropping systems were collected from long-term location experiment station, Changwu County, Shaanxi Province. The changing conditions of exchangeable Mg in soil profiles of different cropping systems under the condition of 22 years' continuous application of NP chemical fertilizer in Loess Plateau were studied. The results showed that the exchangeable Mg occurred eluviation and accumulation in soil profiles of different cropping systems. The peak was at 60-100 cm soil depth with the values of 263, 255, 250, 248, 244 and 243 mg·kg-1 under the sainfoin-wheat (2 a) rotation, wheat (2 a) + millet-maize rotation, maize-wheat (2 a) + millet rotation, pea-wheat (2 a) + millet rotation, wheat succession and pea-wheat (2 a) + maize rotation systems, respectively. The cumulative amounts of exchangeable Mg in soil profiles (0-200 cm) under the sainfoin-wheat (2 a) rotation, wheat (2 a) + millet-maize rotation, pea-wheat (2 a) + millet rotation, maize-wheat (2 a) + millet rotation, pea-wheat (2 a) + maize rotation and wheat succession were 6 152, 5 855, 5 853, 5 755, 5 740 and 5 347 kg·hm-2, respectively. The results suggest that the different crops and cropping systems have effects on difference of exchangeable Mg distribution and accumulation in soil profile.